Glacial-interglacial changes in oceanic conditions and depositional process in the continental rise in response to ice sheet (shelf) variation in Bellingshausen Sea, Antarctica - Kim, Sunghan; Bak, Young-Suk; Prebble, Joseph G.; Kang, Myung-Il; Kim, Sookwan; Park, Jinku; Lee, Min Kyung; Lee, Jae Il; Yoo, Kyu-Cheul; Moon, Heung Soo (Frontiers in Marine Science, 2023)
Antarctic continental margin sediments are eroded from the shelf and transported to the slope/rise in association with changing ice sheet configuration. Understanding the dynamics of this transport pathway is important for utilizing distal deep-sea sedimentary archives to determine past changes in the Antarctic ice sheet. However, these connections are poorly understood. Here we present multi-proxy records of two cores from the Bellingshausen Sea continental rise, to explore relationships between depositional regime and ice sheet dynamics. Two cores showed depositional/sedimentological variations on glacial-interglacial scales. Biogenic sediments were deposited during MIS 1, 5, and 7 under open ocean conditions. Glacial to deglacial sediments were laminated as a result of varying intensity of bottom currents. Terrestrially derived sediments are inferred to be transported from shelf both as grounded ice advanced during glacial expansion, and as ice retreated during deglacial periods. Sediment color shifted to brown after deglacial periods with high Mn/Ti and occurrence of bioturbation, indicating increasing bottom water oxygenation in the study area. Since surface water production started to increase from deglacial periods, we infer increased bottom water oxygenation in this setting is due to ventilation (i.e., Antarctic Bottom Water (AABW) formation), implying that AABW formation was increased during interglacial periods from deglacial period whereas was decreased during glacial periods. Thus, sedimentary/depositional changes in BS17-GC01 and BS17-GC02 are closely linked to ice sheet dynamics during the late Quaternary.